PENGARUH PARTISIPASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING PADA DINAS PENDIDIKAN ACEH - Eliana Eliana; Intan Novia Astuti; Nurhayati Nurhayati; Rini Gusmadiana (SI-MEN, 2021)
The purpose of this study was to determine the effect of budgetary participation on managerial performance, the effect of budget target clarity on managerial performance, organizational commitment to moderate the effect of budget participation on managerial performance, organizational commitment to moderate the effect of budget target clarity on managerial performance and to determine the effect of budget participation and clarity. budget targets simultaneously on managerial performance at the Aceh Education Office. The technique of determining the research sample uses the census method where the entire population is used as a research sample, namely the head, secretary, head of subsection, head of division and love, totaling 62 people. The technique of distributing questionnaires in this study was carried out by personally administered questionnaires. Data analysis in this study used simple linear regression analysis and Moderated Regression Analysis with SPSS 20. Based on the results of the study, it was found that (1) budget participation had a positive and significant effect on managerial performance, (2) clarity of budget targets had a positive and significant effect on managerial performance. (3) organizational commitment moderates (strengthens) the positive and significant influence between budget participation on managerial performance (4) organizational commitment moderates (strengthens) the positive and significant effect between the clarity of budget goals on managerial performance, and (5) simultaneous testing shows that Fcount = 22,994 with a correlation coefficient of 89.5% which states that budget participation and clarity of budget targets simultaneously have a positive and significant effect on managerial performance at the Aceh Education Office.